2020
DOI: 10.1109/access.2020.3026452
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Retrieval System for Biomedical Images Based on Radial Associated Laguerre Moments

Abstract: The ability of any retrieval system to extract features by using its feature descriptor is the primary criterion to measure its efficiency. In this paper a novel technique for feature extraction of biomedical images is presented. The mooted system uses the Radial Associated Laguerre Moments (RALMs) as a feature descriptor to obtain features from two types of medical images: computer tomography (CT) and magnetic resonance images (MRI). RALMs represent one sort of discrete orthogonal moments. RALMs extract the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Results of retrieval are used for retuning the model, and estimating the best hyperparameters for efficient model performance. Due to which, the proposed model is 18% more accurate than GRH [2], 36% more accurate than RaLM [5], and 34% more accurate than DHV [16], while it has 14% more recall than GRH [2], 19% more recall than RaLM [5], and 29% more recall than DHV [16] for different types of medical images. Similar observations were obtained for precision, fMeasure and AUC performance, which indicates that the model is useful for a wide variety of medical image retrieval applications.…”
Section: Conclusion and Future Scopementioning
confidence: 97%
See 2 more Smart Citations
“…Results of retrieval are used for retuning the model, and estimating the best hyperparameters for efficient model performance. Due to which, the proposed model is 18% more accurate than GRH [2], 36% more accurate than RaLM [5], and 34% more accurate than DHV [16], while it has 14% more recall than GRH [2], 19% more recall than RaLM [5], and 29% more recall than DHV [16] for different types of medical images. Similar observations were obtained for precision, fMeasure and AUC performance, which indicates that the model is useful for a wide variety of medical image retrieval applications.…”
Section: Conclusion and Future Scopementioning
confidence: 97%
“…Each Parametric analysis in terms of accuracy (A), precision (P), recall (R), area under the curve (AUC), and fMeasure (F) values. Each of these parameters are estimated for GRH [2], RaLM [5], DHV [16] From the precision evaluation, it is observed that the proposed model is 14% more precise than GRH [2], 16% more precise than RaLM [5], and 24% more precise than DHV [16] for different types of medical images. This improvement in precision is due to use of application specific retrieval method selection, which makes the model highly useful for clinical applications.…”
Section: Design Of Performance Validation and Model Retuning Unit Usi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the literature on image analysis techniques indicates that the method of orthogonal moments plays a significant role in each of its important fields. These fields include image reconstruction [1,2], face recognition [3], image classification [4,5], image watermarking [6], image encryption [7], image compression [8,9]. Orthogonal moments are classified as continuous or discrete depending on whether the kernel functions are orthogonal in the continuous or discrete domain.…”
Section: Introductionmentioning
confidence: 99%
“…Square Error (MSE): the reconstruction error between the original and reconstructed signals. 𝑠(𝑥) − 𝑆(𝑥))2 …”
mentioning
confidence: 99%